Transition of extractive industry governance: Effort towards an inclusive green economy - Sholikin, Ahmad; Erison, Yendra; Rohmah, Eva Nur Laily (Jurnal Sosiologi Dialektika, 2025)
The transition of extractive industry governance is one of the major challenges in realizing an inclusive green economy, especially in regions with a high dependency on this sector, such as Bojonegoro Regency. This study aims to analyze the efforts of Bojonegoro in transitioning the governance of extractive industries towards the implementation of an inclusive green economy, considering the dimensions of environmental sustainability, community participation, and economic growth. The research adopts a qualitative approach, with primary data analysis through in-depth interviews and secondary data from policy documents, official reports, and related literature. The findings indicate that the Bojonegoro local government has initiated various programs to improve the sustainability of the industry, such as economic diversification, capacity building for local communities, and strengthening environmental regulations. However, significant challenges remain, including fiscal dependence on revenues from the oil and gas sector and resistance from certain stakeholders. The study concludes that the success of the transition towards an inclusive green economy requires a more holistic policy integration, collaboration among stakeholders, and strengthening the role of local communities in decision-making. Recommendations include the formulation of long-term policies for local economic diversification, the development of renewable energy, and enhanced oversight of the environmental impacts of extractive activities. These findings are expected to serve as a reference for local governments and other stakeholders in developing sustainable and inclusive transition strategies.